Physicochemical Properties of Milkfish Gelatin-Natural Starch Composite - Ismail, Isriany; Djide, M. Natsir; Manggau, Marianti A.; Rahman, Latifah (Open Access Macedonian Journal of Medical Sciences, 2022)
Halal gelatin sourced from fish can be improved in quality through mixing with other polymers so that it can be an alternative as food, pharmaceutical, and cosmetic ingredient. The purpose of this study was to determine the characteristics of milkfish scale gelatin after the formation of a composite with corn, potato, and cassava starch to be used as a pharmaceutical and food excipient. The gelatin composite (FMG) of milkfish scales with corn, potato, and cassava starch (GM, GS, and GC) was made by casting method, using a ratio of gelatin and starch (4,5:0,5). Characteristic assessment includes organoleptic, viscosity, swelling index, FT-IR spectroscopy, and Calorimetry (DSC). Data analysis used a non-parametric One Way ANOVA statistical method (p<0.05). The composites produced from mixing FMG with corn starch (GM), potato (GS) and cassava (GC) showed hygroscopic properties, increased viscosity values and decreased swelling index in GM (7.89 cP & 25.0%), GS (8 .36 cP & 21.0%), and GC (8.64 cP & 12.7%), compared to FMG (0.11 cP & 75%) at p < 0.05. The behavior of the composite FT-IR spectrum follows the FMG spectrum pattern with a shift in wavenumber in the typical bands (Amide A, Amide B, Amide I, Amide II, and Amide III) in the gelatin spectrum. There was a shift of Tg to higher values in GM and GS, Tm increased in GM and GC, and all composites showed a decrease in melting enthalpy. The spectral pattern of the composite follows the typical spectral pattern of FMG. GM, GS, and GC composites showed increased viscosity, water retention, and thermal stability compared to FMG. GM and GS may be used as pharmaceutical and food excipients.